Kecerdasan Intelektual Dalam Perspektif Al-Qur’an - M. Dwi Rahman Sahbana; Ahmad Arifi; Taufik Rahman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to analyze Intellectual Intelligence in the perspective of the Qur'an. This research uses the method of library research (library research), namely research whose subject is in the form of library literature. The author collects books and scientific journals that are needed and then studied. Furthermore, the author cites various theories and opinions related to the problem under study. Sources of data depart from documentation that comes from books and scientific journals that discuss intellectual intelligence in the perspective of the Qur'an. The results of this study say that intelligence is an added value for every human being in developing his mindset so that he is able to develop and think clearly to consider, decide and deal with things by focusing on the problems faced with brilliant solutions. The process of growing intellectual intelligence according to Islamic education is marked by the existence of moral education. The intellectual intelligences possessed by humans as described in the Qur'an provide a clear picture that humans were created by Allah SWT and are given extraordinary potential in the form of reason and mind which will make a difference between humans and Allah's creatures. the other, with the potential it has, it is important to understand and study the holy book of the Qur'an and study every verse in it so that it always has a positive impact in developing one's intellect by understanding the verses of Allah SWT. With that, the potential possessed by humans will run according to the guidance of the Qur'an.